DEVELOPMENT OF STUDENT ACTIVITY SHEETS (LAPD) USING A MIND MAPPING STRATEGY TO TRAIN CREATIVE THINKING SKILLS ON CHEMICAL EQUILIBRIUM MATERIAL - Adelia Fourista Khairiniza; Mitarlis Mitarlis (Universitas Negeri Surabaya, 2026)
This study was conducted to determine the feasibility of Student Activity Sheets or LAPD designed with a mind mapping strategy to improve students’ creative thinking skills in the topic of chemical equilibrium. The research applied the 4D development model consisting of the define, design, develop, and disseminate stages, but its implementation was limited to the develop stage. The product was tested on 35 eleventh grade students at a public senior high school. The feasibility evaluation covered three aspects, namely validity, practicality, and effectiveness. The results showed that the LAPD fulfilled the validity criteria, as all components of content and construct validity achieved a mode score equal to or greater than 4. Practicality was reflected in the high percentage of relevant student activities at 97.10 percent and positive student responses at 88.54 percent, both categorized as very practical. Effectiveness was indicated by the improvement in students’ creative thinking skills based on the comparison of pretest and posttest results from mind mapping assessments and essay tests, which produced average N gain scores of 0.76 and 0.72, respectively, both classified in the high category. Therefore, the mind mapping based LAPD can be considered feasible and effective in enhancing students’ creative thinking skills in chemical equilibrium learning